NMDA Receptors Regulate the Development of Neuronal Intrinsic Excitability through Cell-Autonomous Mechanisms - Hou, Guoqiang; Zhang, Zhong-Wei (Frontiers in Cellular Neuroscience, 2017)
Maturation of neuronal and synaptic functions during early life is essential for the development of neuronal circuits and behaviors. In newborns synaptic transmission at excitatory synapses is primarily mediated by N-methyl-D-aspartate receptors (NMDARs), and NMDAR-mediated signaling plays an important role in synaptic maturation. Concomitant with synapse development, the intrinsic properties of neurons undergo dramatic changes during early life. However, little is known about the role of NMDARs in the development of intrinsic excitability. By using mosaic deletion of the obligatory GluN1 subunit of NMDARs in the thalamus of newborn mice, we showed that NMDARs regulate neuronal excitability during postnatal development. Compared with neighboring control neurons, neurons lacking NMDARs exhibit hyperexcitability and this effect is present throughout early life. Morphological analyses show that thalamic neurons without NMDARs have smaller soma size and fewer dendritic branches. Deletion of NMDARs causes a reduction of hyperpolarization-activated cation (HCN) channel function in thalamic neurons, and pharmacologically blocking HCN channels in wild type neurons mimics the effects of GluN1 deletion on intrinsic excitability. Deletion of GluN1 down-regulated mechanistic target of rapamycin (mTOR) signaling in thalamic neurons, and mosaic deletion of mTOR recapitulated the effects of GluN1 deletion. Our results demonstrate that NMDARs regulate intrinsic excitability and morphology of thalamic neurons through cell autonomous mechanisms that implicate mTOR signaling.